Analisis Permasalahan Standar Proses Kurikulum 2013 Pada Masa Pandemi Covid-19 - Masruroh, Siti; Suprapti (Jurnal Simki Pedagogia, 2020)
This research was motivated by implementation of the standard 2013 curiculum process during the Covid-19 pandemic which gave rise to new problems when carrying out standard processes in the 2013 curriculum during the Covid-19 pandemic at MI Muhammadiyah Klaseman Gatak Sukoharjo. The purpose of this study was to analyze the standard of the 013 curriculum process during the Covid-19 pandemic at MI Muhammadiyah Klaseman starting from the planning, implementatiton, to learning assessmnt stages. The subject of this study was the head of the madrasah MI Muhammadiyah Klaseman, the informants of this study were teachers and students at the madrasah. This research is a field reseach eith qualitative method. Data collection techniques with observation, interviews, and dokumentatiton. The results showed that in carrying out teaching and learning activities based n process standards in the 2013 curriculum during the panemic there were problems: (1) at the learning planning satge, the teacher was not prepared toimplementation the 2013 curriculum during the pandemic; (2) the implemetation stage of learning is inadequate fasiities and infrastrukture, the difficulty of teacher in monitring the condition of students in online learning, students are not familiar with learning online; (3) at the learning assessment stage the problem is the teacher has difficulty in assessing student learning outcomes.